2020
DOI: 10.3390/pharmaceutics12050479
|View full text |Cite
|
Sign up to set email alerts
|

Injectable SN-38-embedded Polymeric Microparticles Promote Antitumor Efficacy against Malignant Glioma in an Animal Model

Abstract: Malignant glioma (MG) is extremely aggressive and highly resistant to chemotherapeutic agents. Using electrospraying, the potent chemotherapeutic agent 7-ethyl-10-hydroxycamptothecia (SN-38) was embedded into 50:50 biodegradable poly[(d,l)-lactide-co-glycolide] (PLGA) microparticles (SMPs). The SMPs were stereotactically injected into the brain parenchyma of healthy rats and intratumorally injected into F98 glioma-bearing rats for estimating the pharmacodynamics and therapeutic efficacy. SN-38 was rapidly rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…However, the high toxicity and instability of SN-38 in the physiological environment (pH 7.4) have made its clinical use infeasible [ 28 ]. In our previous study, we demonstrated that SMP-based interstitial delivery of SN-38 is feasible [ 31 ]. This therapeutic strategy, combined with orally administered TMZ, displayed increased anti-tumor activity in a rat model of malignant glioma.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the high toxicity and instability of SN-38 in the physiological environment (pH 7.4) have made its clinical use infeasible [ 28 ]. In our previous study, we demonstrated that SMP-based interstitial delivery of SN-38 is feasible [ 31 ]. This therapeutic strategy, combined with orally administered TMZ, displayed increased anti-tumor activity in a rat model of malignant glioma.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we loaded SN-38 into poly(lactid-co-glycolid) (PLGA) microparticles (SMPs) using an electrospraying technique. SMPs were introduced into rat brain parenchyma via stereotactic techniques [ 31 ]. Our previous results suggested that SMPs are biocompatible and biodegradable [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations